Study of structural properties of copper nanotubes modified with ionizing radiation - Kenzhina, I.; Kozlovskiy, A.; Kadyrzhanov, K.K. (Recent Contributions to Physics, 2018)
In modern materials science, irradiation with electron beams and a γ ray flux of metallic nanostructures is an effective tool for stimulating a controlled modification of structural and conductive properties of materials. The paper presents the results of the influence of various types of irradiation on structural and conductive properties of copper nanotubes obtained by electrochemical synthesis in pores of template matrices based on polyethylene terephthalate. The modification of properties of synthesized Cu-nanotubes was carried out at ELV-4 linear accelerator (Kurchatov, Kazakhstan) by irradiating with electrons flux of 5 MeV energies and γ quanta with of 1.35 MeV energy, doses of 50-250 kGy in 50 kGy increments. SEM, XRD and EDS methods established that irradiation with an electron beam and γ rays with doses of 50 and 100 kGy allows us modifying the crystal structure of nanotubes, increasing their conductivity and decreasing their resistance without destroying their structure. An increase in the irradiation dose leads either to an insignificant change in conductive properties for high-energy electrons and γ quanta, or to a deterioration of conductive properties due to the appearance of oxide compounds in the crystal structure and subsequent destruction of samples.